2020
DOI: 10.7150/ijbs.41246
|View full text |Cite
|
Sign up to set email alerts
|

ATM Expression Is Elevated in Established Radiation-Resistant Breast Cancer Cells and Improves DNA Repair Efficiency

Abstract: Repair of damaged DNA induced by radiation plays an important role in the development of radioresistance, which greatly restricts patients' benefit from radiotherapy. However, the relation between radioresistance development and DNA double-strand break repair pathways (mainly non-homologous end joining and homologous recombination) and how these pathways contribute to radioresistance are unclear. Here, we established a radioresistant breast cancer cell line by repeated ionizing radiation and studied the altera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…To find the difference between the RR and RS groups, we utilized GSVA to distinguish the biological function of the RR and RS samples (Figure 2A). Based on GSVA analysis, we found that the functional difference between RS and RR patients was associated with extracellular matrix (ECM) and DNA-related functions, which was consistent with previous reports (Ljungman, 2009;Bian et al, 2020;Haeger et al, 2020). Interestingly, two immune-related terms, immunoglobulin receptor binding and CD22-mediated BCR regulation (Figure 2A), were observed in the list of the top 25 terms enriched in the RR or RS groups, indicating that the immune microenvironment is involved in the RT response.…”
Section: Identification Of Rt-related Gene Function and Tumor Immune Environmentsupporting
confidence: 91%
“…To find the difference between the RR and RS groups, we utilized GSVA to distinguish the biological function of the RR and RS samples (Figure 2A). Based on GSVA analysis, we found that the functional difference between RS and RR patients was associated with extracellular matrix (ECM) and DNA-related functions, which was consistent with previous reports (Ljungman, 2009;Bian et al, 2020;Haeger et al, 2020). Interestingly, two immune-related terms, immunoglobulin receptor binding and CD22-mediated BCR regulation (Figure 2A), were observed in the list of the top 25 terms enriched in the RR or RS groups, indicating that the immune microenvironment is involved in the RT response.…”
Section: Identification Of Rt-related Gene Function and Tumor Immune Environmentsupporting
confidence: 91%
“…These two main DSBs repair pathways play an indispensable role in initiating and processing cancer. Patients harboring deficiencies affecting HR or NHEJ often present increased susceptibility towards cancer [ 127 , 145 , 146 , 147 ].…”
Section: Countermeasuresmentioning
confidence: 99%
“…For radiation-inducing cytotoxic activity of CD8+ T cells through the release cytotoxic proteins, the principal mechanism through which cytotoxic T cells act is by the calcium-dependent release of specialized lytic granules upon recognition of antigen on the surface of a target cell. These granules are modified lysosomes that contain at least two distinct classes of cytotoxic effector protein that are expressed selectively in cytotoxic T cells [ 147 ].…”
Section: Countermeasuresmentioning
confidence: 99%
“…This might contribute to radioresistance as the arrest in the cell cycle provides time for the damaged DNA to be repaired, allowing cancer cells to continue proliferating (Gogineni et al 2011;. Therefore, radioresistant cancer cells can also exhibit enhanced DNA damage repair capacity, as evidenced by the upregulation of key genes involved in DNA repair pathways such as Chk1 (Jiang et al 2019), ATM (Bian et al 2020), RAD1, BRCA1, and BRCA2 (Balbous et al 2016).…”
Section: Mechanism Of Action Of Radiotherapy and The Development Of Radioresistancementioning
confidence: 99%